Modern Methods of Treating Nosebleeds - Qiyomov Ixtiyor Ergashevich (Journal of Science in Medicine and Life, 2024)
Epistaxis is the most common type of external bleeding, accompanied by a runny nose, often associated with facial trauma, and occurs in both adults and children. Most often, damage to blood vessels occurs in the area of the nasal septum. The development of bleeding from the structures at the back of the nose often occurs in patients with atherosclerosis, blood diseases, or during surgery on the nose for therapeutic or aesthetic purposes.